Application of observational research methods to real-world studies for rare disease drugs: A scoping review protocol. - Yuti P Patel; Lea Ghaddar; Yuqi Lin; Nuzat Karim; Kelvin Chan; Lee Dupuis; Mina Tadrous (PLoS ONE)
The primary objective is to identify which observational research methods have been used in the last 5 years in rare disease drug evaluation and how they are applied to generate adequate evidence regarding the real-world effectiveness or safety of rare disease drugs. Rare disease is an umbrella term for a condition which affects < 200,000 people each year and despite the rarity of these conditions, collectively they encompass approximately 7000 different conditions. With the striking number of rare conditions, many pharmaceutical manufacturers are introducing an increased number of drugs to treat them. However, due to small patient populations, heterogeneity and other factors related to rare diseases, there are feasibility concerns regarding the generation of adequate efficacy and safety evidence using conventional randomized controlled trials (RCTs). Recently, real-world evidence generated through observational (or real-world) studies has been proposed to address some of the feasibility concerns with RCTs by measuring drug effectiveness or safety in the real-world setting. However, there remain methodological concerns due to a lack of randomization/masking. This proposed scoping review aims to identify which observational research methods in the last 5 years are used in rare disease drug evaluation to address methodological concerns and how they are applied to generate evidence on drug effectiveness or safety. Articles must be primary observational or real-world studies reporting rare disease drug effectiveness or safety published within the five years preceding this review. Literature reviews, meta-analyses, randomized control trials, case series, case reports, opinion pieces, conference abstracts, and studies with unavailable full-text articles will be excluded. The search strategy will combine the following key search concepts: rare disease, drugs for rare disease and observational/real-world studies. The search will be conducted in MEDLINE and EMBASE. Review registration number: Open Science Framework, https://osf.io/f3wpv.